A Case Study of the Construction of the Hanura Party's "Religious Nationalist" Ideology in Medan City - Amri, Syaiful; Situmorang, Tonny P.; Ginting, Bengkel (PERSPEKTIF, 2025)
This article or paper aims to analyze the ideological construction of the Hanura Party, namely "Religious Nationalist," about the regeneration process in Medan. In addition, this study also aims to evaluate the electability of candidates for the Hanura Party legislative members in Medan City by applying the ideology of "Religious Nationalists." This study uses a qualitative research method with a type of descriptive research, using primary and secondary data collection techniques. Primary data in this Thesis was obtained through interviews and observations, while secondary data was obtained through books, journals, and the Internet. Research shows that the religious nationalist ideology of the Hanura Party plays a vital role in shaping the political identity, loyalty, and ethics of cadres in the city of Medan. However, the challenge of internalizing ideology underscores the need to strengthen the regeneration program, especially in connecting ideological teaching with field practice. The success of cadre regeneration requires the development of technical competence to deal with political dynamics, so the Hanura Party needs to innovate in forming cadres who are loyal to ideology and politically competent.